Isolation and purification of monosialotetrahexosylgangliosides from pig brain by extraction and liquid chromatography. (6th April 2015) - Bian, Liujiao; Yang, Jianting; Sun, Yu
Abstract Monosialotetrahexosylganglioside (GM1), one of glycosphingolipids containing sialic acid, plays particularly important role in fighting against paralysis, dementia and other diseases caused by brain and nerve damage. In this work, a simple and highly efficient method with high yield was developed for isolation and purification of GM1 from pig brain. The method consisted of an extraction by chloroform–methanol–water and a two‐step chromatographic separation by DEAE–Sepharose Fast Flow anion‐exchange medium and Sephacryl S‐100 HR size‐exclusion medium. The purified GM1 was proved to be homogeneous and had a purity of >98.0% by high‐performance anion‐exchange and size‐exclusion chromatography. The molecular weight was 30.0 kDa by high‐performance size‐exclusion chromatography and 1546.9 Da by electrospray ionization mass spectrometry. The chromogenic reaction by resorcinol–hydrochloric acid solution indicated that the purified GM1 showed a specific chromogenic reaction of sialic acid. Through this isolation and purification program, ~1.0 mg of pure GM1 could be captured from 500 g wet pig brain tissue and the yield of GM1 was around 0.022%, which was higher than the yields by other methods. The method may provide an alternative for isolation and purification of GM1 in other biological tissues. Copyright © 2015 John Wiley & Sons, Ltd.